Sistem Informasi Akademik SMP Santa Veronika Berbasis Web - Nadia Sita; Elvira Asril (LPPM STMIK Royal Kisaran, 2022)
Abstract: The academic information system at Santa Veronika Junior High School is still done manually. In processing academic data, it is still conventional with a data collection system, which is now felt to have many shortcomings that occur because the existing system still uses sheets of paper and archives so that it can cause existing data to be easily lost or damaged. System development in the form of making a web-based academic information system at Santa Veronika Junior High School is a system that provides online student report information in the form of web-based student grade reports, thus helping speed and quality in delivering information. In addition, with a web-based, data information can be accessed at an unspecified time and place. In this system, the menu can only be accessed by certain users, namely admin, teacher, homeroom teacher, students, principal. In this study, apart from describing the theoretical study used as the basis for the preparation, it will also discuss system design and information system creation. System can be implemented in a product that will fix all the shortcomings that exist in the old system. Keywords: academic; school; junior high school Abstrak: Sistem informasi akademik pada SMP Santa Veronika masih dilakukan secara manual. Dalam pengolahan data akademik masih secara konvensional dengan sistem pendataan yang sekarang dirasakan masih banyak kekurangan yang terjadi dikarenakan sistem yang ada masih menggunakan lembaran kertas dan arsip sehingga dapat menyebabkan data-data yang ada mudah hilang ataupun rusak. Pengembangan sistem berupa pembuatan sistem informasi akademik berbasis web pada SMP Santa Veronika merupakan sistem yang memberikan informasi laporan siswa secara online yang berupa laporan nilai siswa yang bersangkutan dengan berbasis web, sehingga membantu kecepatan dan kualitas dalam penyampaian informasi. Selain itu dengan berbasis web maka informasi data dapat diakses dengan waktu dan tempat yang tidak ditentukan. Pada sistem ini, menu hanya dapat diakses oleh user tertentu yaitu admin, guru, walikelas, siswa, kepala sekolah. Dalam penelitian ini selain memaparkan kajian teori yang digunakan sebagai dasar penyusunan, juga akan dibahas mengenai perancangan sistem dan pembuatan sistem informasi. Hasil dari yang dibuat dapat membantu akademik dalam pendataan laporan dan memperbaiki segala kekurangan yang ada pada sistem yang lama. Kata Kunci : akademik; sekolah; SMP